Advances in Drug Resistance Mechanisms and Prognostic Markers of Targeted Therapy in ALK-positive Non-small Cell Lung Cancer - Shasha WANG (Chinese Journal of Lung Cancer, 2020)
Echinoderm microtubule-associated protein like 4-anaplastic lymphoma kinase (EML4-ALK) fusion accounts for 3%-5% of non-small cell lung cancer (NSCLC) patients. With the in-depth study of the EML4-ALK driver gene, ALK inhibitors represented by crizotinib have been gradually developed and applied in the clinic. However, the response to ALK-targeted therapy is heterogeneous among different patients. Most patients with ALK-targeted therapy will inevitably develop drug resistance, leading to tumor progression. Monitoring the efficacy of patients with prognostic markers to change the treatment in time, and selecting individualized follow-up treatment according to the mechanism of drug resistance, can effectively improve the prognosis of patients. This article will review the mechanism of ALK tyrosine kinase inhibitor (ALK-TKI) resistance and related prognostic markers to discuss the prediction for ALK-targeted therapy and the choice of subsequent treatment for drug-resistant patients.